Adsorption and growth of palladium clusters on graphdiyne. Issue 29 (12th July 2017) - Seif, A.; López, M. J.; Granja-DelRío, A.; Azizi, K.; Alonso, J. A.
Abstract : The density functional formalism has been used to investigate the stability and the properties of small palladium clusters supported on graphdiyne layers. Abstract : The density functional formalism has been used to investigate the stability and the properties of small palladium clusters supported on graphdiyne layers. The large triangular holes existing on the graphdiyne structure provide efficient sites to hold the clusters at small distances from the plane of the graphdiyne layer. The cluster adsorption energies, between 3 and 4 eV, are large enough to maintain the clusters tightly bound to the triangular holes. The competition between dispersion of Pd atoms on graphdiyne and growth of Pd clusters in the triangular holes of the layer is also discussed. In addition, the triangular holes can be simultaneously decorated with clusters on both sides. This indicates that palladium clusters could be used to build nanostructures formed by stacked graphdiyne layers with tailored interlayer distances controlled by the size of the clusters. The size of the clusters also controls the electronic HOMO–LUMO gap of the material.